2021
DOI: 10.1007/s43545-021-00080-2
|View full text |Cite
|
Sign up to set email alerts
|

Cultural values predict national COVID-19 death rates

Abstract: National responses to a pandemic require populations to comply through personal behaviors that occur in a cultural context. Here we show that aggregated cultural values of nations, derived from World Values Survey data, have been at least as important as top-down government actions in predicting the impact of COVID-19. At the population level, the cultural factor of cosmopolitanism, together with obesity, predict higher numbers of deaths in the first two months of COVID-19 on the scale of nations. At the state… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Thus, our study demonstrates that flexibility-monumentalism is a unique national cultural trait that explains cross-country variations in COVID-19 mortality in 2020. The study contributes new evidence to the existing literature on the relationship between national culture and COVID-19 infection and death rates (Salvador et al, 2020;Dheer et al, 2021;Gelfand et al, 2021;Gokmen et al, 2021;Güss and Tuason, 2021;Kumar, 2021;Ozkan et al, 2021;Ruck et al, 2021;Schopf, 2022).…”
Section: Main Findingsmentioning
confidence: 70%
See 1 more Smart Citation
“…Thus, our study demonstrates that flexibility-monumentalism is a unique national cultural trait that explains cross-country variations in COVID-19 mortality in 2020. The study contributes new evidence to the existing literature on the relationship between national culture and COVID-19 infection and death rates (Salvador et al, 2020;Dheer et al, 2021;Gelfand et al, 2021;Gokmen et al, 2021;Güss and Tuason, 2021;Kumar, 2021;Ozkan et al, 2021;Ruck et al, 2021;Schopf, 2022).…”
Section: Main Findingsmentioning
confidence: 70%
“…Several studies have shown that national cultural traits predict COVID-19 infection and mortality rates (Salvador et al, 2020;Dheer et al, 2021;Gelfand et al, 2021;Gokmen et al, 2021;Güss and Tuason, 2021;Ozkan et al, 2021;Ruck et al, 2021): collectivism and tight social norms are associated with lower rates of COVID-19 infections and deaths, whereas cosmopolitanism is associated with higher infection and mortality rates. Scholars have also examined other prominent national cultural traits and COVID-19 infection and/or mortality rates and found significant associations between them.…”
Section: Introductionmentioning
confidence: 99%
“…Auto, aviation, shipbuilding, and other industries have been drawn into a severe recession. Even though a number of researchers argue that the stability of values is relatively high and their restructuring over a short period of time (that is, over the course of the coronavirus pandemic) is impossible [Giavazzi et al, 2014], others rest on the belief that the impact of pandemics on cultural values is significant [Barro et al, 2020;Ruck et al, 2021].…”
Section: Inglehart and Welzel's Mapmentioning
confidence: 99%
“…The depth of a recession influences perceptions of economic and physical security concerns, the level of people's trust in government, lifestyle patterns, and their willingness to invest their own money in universal healthcare systems. Or, as the authors of the article "Cultural Values Predict National COVID-19 Death Rates" note, governments in more tolerant and democratic countries are having difficulty mitigating the effects of the COVID-19 pandemic because the population and institutions of these countries are characterized by self-expression values instead of survival [Ruck et al, 2021].…”
Section: Introductionmentioning
confidence: 99%
“…There are also many other determinants in literature describing the different relationships between COVID contagion and death rate as prevalence of Black and Hispanic populations (Cheng et al 2020), partisanship (Gadarian et al 2021), average Y-DNA haplogroup percentages (Delanghe et al 2020;Ibrahim -Salih 2021;Schillaci 2021), cosmopolitanism, government efficiency and public trust in institutions (Dinc a et al 2020;Ruck et al 2021), transport infrastructure quality score (Liang et al 2020), commuting via public transportation and driving into work (relative to telecommuting), higher home values, higher summer temperatures and lower winter temperatures (Knittel -Ozaltun 2020), density of the population (Doti 2020), households with a mortgage, land cover with forest, people living in group quarter and airborne benzene concentration (Luo et al 2021) and so on. These indicators should be considered in the overall assessment of the COVID pandemic, but from the perspective of this study, their impact on CFR should be negligible.…”
Section: Literature Reviewmentioning
confidence: 99%